2019
DOI: 10.18203/2349-2902.isj20192949
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intravenous tranexamic acid on reduction of seroma after para- umbilical hernioplasty

Abstract: Background: Para-umbilical hernioplasty is mostly safe but there are possible complications like seroma, wound infection and recurrence. Tranexamic acid is a synthetic derivative of the amino acid lysine that exerts an anti-fibrinolytic action through the reversible blockade of lysine binding sites on plasminogen molecules, used in the prevention and treatment of excessive bleeding both in primary and secondary care. Our study aimed to evaluate the effect of intravenous tranexamic acid injection on reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…Even in patients with mastectomy tranexamic acid has well established role (23,24). Albatonanny has also found reduced risk among patients with single use of tranexamic acid in patients with ventral hernia (12). Use of Tranexamic acid in our study reduced postoperative drain output in patients with ventral hernia repair.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Even in patients with mastectomy tranexamic acid has well established role (23,24). Albatonanny has also found reduced risk among patients with single use of tranexamic acid in patients with ventral hernia (12). Use of Tranexamic acid in our study reduced postoperative drain output in patients with ventral hernia repair.…”
Section: Discussionsupporting
confidence: 70%
“…Studies have shown postoperative reduction in complications when tranexamic acid was used in patients of ventral hernia with reduced seroma formation, serous discharge and postoperative wound leakage as reported previously (16)(17)(18)(19)(20). A Study by Ahmed et al has found 81% patients with seroma formation but reduced in 5 days postoperatively and reduced drain output with use of tranexamic acid 1gm twice daily with short hospital stay (20).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It can be the reason for postoperative wound infection, suppuration and hernia recurrence. 6 We had all our patients operated on by a fixed team of surgeons divided into two groups; group 1 with mesh repair and group 2 with only anatomical repair without mesh. All patients completed a 6-month follow-up period with interval reviews for detection of any complications.…”
Section: Discussionmentioning
confidence: 99%